Wrap & Plant Technology: An Innovative and Cost-Effective Method for Seed Yam Treatment for Nematode Control in Fields - Dedehouanou, Houinsou (Advances in Social Sciences Research Journal, 2022)
ABSTRACT In West Africa, seed yam represents an important source of nematode inoculums in yam fields and a major cause of the disease perpetuation. To enhance nematode control on yam (Dioscorea spp.), a pilot participatory field evaluation was conducted in Benin on nematode control potential of abamectin-treated banana paper (treatment A) using seed wrap method. An additional seed yam wrapped with untreated paper (treatment B) is also considered. Both treatments A & B are then compared to unwrapped seed yam representing the farmers’ practice (FP). In each field, plots are arranged in a randomized complete block design with five replicates. The effects of seed yam treatment on nematode control in fields, gustatory qualities of yam tubers, and both social and profitability studies of the technology were assessed. In the present paper, only the study related to the profitability based on the Net Margin (NM) and the ratio Cost/Profit is presented. Results reveal advantages of treatments A and B over (FP). In fact, production statistics from treatments A and B are significantly higher than those from (FP). Based on the "willingness to pay" approach, the profitability study shows that treatment A has a Net Margin of approximately 153.7% that of (FP). Concerning the ratio Cost/Profit, 100 FCFA (West African CFA franc) spent in yam production using this new technology generates around 79.3 FCFA against 59.9 FCFA for (FP). Despite the success of this pilot study, input prices must be monitored before scaling up this innovation to the other agro-ecological regions of Benin. Key-words: Nematode control, Dioscorea spp., cost effectiveness, input prices, Wrap & plant technology, Benin